Ekstraksi EKSTRAKSI DAN KARAKTERISASI PEKTIN DARI LIMBAH KULIT JERUK LIMAU (Citrus amblycarpa) - Fiqi Estuning Nava Maulida; Alimuddin Alimuddin; Erwin Erwin (JURNAL KIMIA MULAWARMAN, 2023)
Research on the extraction and characterization of pectin from lemon lime peel waste (Citrus amblycarpa) has been done. The purpose of this research is to process lime waste into raw material of pecti